Concepts and Principles of Photodynamic Therapy as an Alternative Antifungal Discovery Platform - Tegos, George; Dai, Tianhong; Fuchs, Beth B.; Coleman, Jeffrey J.; Prates, Renato A.; Astrakas, Christos; St Denis, Tyler G.; Ribeiro, Martha S.; Mylonakis, Eleftherios; Hamblin, Michael R. (Frontiers in Microbiology, 2012)
Opportunistic fungal pathogens may cause superficial or serious invasive infections, especially in immunocompromised and debilitated patients. Invasive mycoses represent an exponentially growing threat for human health due to a combination of slow diagnosis and the existence of relatively few classes of available and effective antifungal drugs. Therefore systemic fungal infections result in high attributable mortality. There is an urgent need to pursue and deploy novel and effective alternative anti-fungal countermeasures. Photodynamic therapy was established as a successful modality for malignancies and age-related macular degeneration but photodynamic inactivation has only recently been intensively investigated as an alternative antimicrobial discovery and development platform. The concept of photodynamic inactivation requires microbial exposure to either exogenous or endogenous photosensitizer molecules, followed by visible light energy, typically wavelengths in the red/near infrared region that cause the excitation of the photosensitizers resulting in the production of singlet oxygen and other reactive oxygen species that react with intracellular components, and consequently produce cell inactivation and death. Anti-fungal photodynamic therapy is an area of increasing interest, as research is advancing i) to identify the photochemical and photophysical mechanisms involved in photoinactivation; ii) to develop potent and clinically compatible photosensitizers; iii) to understand how photoinactivation is affected by key microbial phenotypic elements multidrug resistance and efflux, virulence and pathogenesis determinants, and formation of biofilms; iv) to explore novel photosensitizer delivery platforms and v) to identify photoinactivation applications beyond the clinical setting such as environmental disinfectants.